The Exact Solution of Vehicle Routing Problem by Mixed Integer Linear Programming in Matlab - Zahrádka, Jaromír (Czech Society for Operations Research, 2023)
This contribution comes up with a specific solution of the vehicle routing problem. The driver has to deliver the goods from the central warehouse to n customers as efficiently as possible. Each customer has ordered goods that fill a certain number of containers. Each customer point of delivery is given by GPS coordinates. The objective of the solution is to select the number of vehicles and their routes between customers in such a way that the total travel time, including the time for unloading the goods, is as short as possible. Each delivery point is visited only once by one of the vehicles. All used vehicles have a pre-limited capacity of containers. All vehicles return to the central warehouse. In this contribution, the algorithm of the exact solution of the vehicle routing problem was created, which can be used in general for any number n of customers. The algorithm is implemented in Matlab code.
Exaktní řešení problému směrování vozidel pomocí smíšeného celočíselného lineárního programování v Matlabu
Keywords: Matlab code; mixed integer linear programming; optimization; point of delivery; vehicle routing problem.; Matlab; smíšené celočíselné lineární programování; optimalizace; místo dodání; problém trasování vozidel.